Islamic Counseling for Reducing Thesis Procrastination on Students of the Islamic Guidance and Counseling Department of UIN Sunan Ampel Surabaya - Fahmi, Lukman; Nuryana, Amiatun (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
In this study, researchers will discuss the behavior that doesn’t appreciate the time or called procrastination particularly in the case of students’ academic procrastination in finishing their thesis. The target of this study is students of the last semester Islamic Guidance and Counseling Department in UIN Sunan Ampel Surabaya for the 2015-2016 academic year. In general, students have a study period of around 3.5 years up to 4 years. But not all students can finish their thesis on time. So, it makes an unrest effect on them. This occurs because it tends to delay their thesis. As a result, many students are unable to finish the thesis program within the specified time for their graduation. Therefore, there needs to be an effort to guide academic procrastination among these students. The Islamic Guidance and Counseling Department Program provides consultation, namely Islamic Counseling Guidance. The purpose of Islamic counseling guidance is to help students, so they do not give up easily in terms of facing their problems. Such as educational problems or personal problems (external or internal) and to help individuals maintain and develop good situations so as not to become a source of problems for themselves and others. The method used in this research is descriptive qualitative with a survey approach. This research refers to the problems or facts that occur. The technique of collecting data is by the survey, interview, and treatment.